Hydrogen content in divertor baffle tiles in Wendelstein 7-X. (March 2021) - Oelmann, Jannis; Wüst, Erik; Brezinsek, Sebastijan; Li, Cong; Zhao, Dongye; Rasinski, Marcin; Dhard, Chandra Prakash; Mayer, Matej; Naujoks, Dirk; Gao, Yu; ,
Abstract: Plasma–wall interactions play a crucial role for the performance of fusion devices and the lifetime of plasma-facing components. In this work the results of some plasma–wall interaction processes, namely the erosion/deposition pattern and the fuel content of divertor baffle tiles exposed in Wendelstein 7-X in the initial phase of island divertor, are presented. Net-deposition of carbon with co-deposited oxygen and hydrogen is determined on the graphite tiles after about 1 hour of plasma operation in hydrogen and helium in operation phase OP 1.2a. C is predominately a result of net-erosion of the graphite target plates and oxygen is the strongest intrinsic impurity in Wendelstein 7-X in OP 1.2a. The hydrogen content distribution on a set of tiles exposed in equivalent positions in three of the five modules of the stellarator was quantified for the first time. Ex-situ performed laser-induced breakdown spectroscopy measurements show the depth-resolved fuel content in deposited layers as well as implantation and diffusion in the base material. Complementary, gas analysis after laser-induced ablation offers quantitative hydrogen content determination in the deposited layers up to 10 18 hydrogen atoms/cm 2 that is non-uniformly distributed over the 95 mm  ×  125 mm sized tiles. The results show a toroidal asymmetry with 60% more hydrogen in the stellarator module 2 with respect to module 1 as well as a slight top-down asymmetry for the baffle tiles in upper and lower half modules. A clear dependence of the hydrogen content on the surface temperature during plasma exposition in stellarator discharges in standard magnetic divertor configuration with edge transformation 5/5 was not observed. Graphical abstract: Highlights: Analyses of divertor baffle tiles exposed in Wendelstein 7-X OP1.2a are presented. The H content distribution for equivalent positions in 4 of 5 modules was quantified. The depth-resolved fuel contents show erosion/deposition pattern and fuel retention. Non-uniformly distributed deposition layers with up to 10 18 H atoms/cm 2 are analyzed. 60% more hydrogen in W7-X module 2 with respect to module 1 baffle tiles is observed.